2019
DOI: 10.21037/atm.2019.02.40
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-200c-3p/ZEB2 loop plays a crucial role in the tumor progression of prostate carcinoma

Abstract: Background: The microRNA (miRNA) miR-200c-3p is involved in the tumorigenesis and progression of a variety of cancers. However, the underlying regulatory role of miR-200c-3p in prostate cancer (PCa) remains unclear. Methods: Online databases including Oncomine, Linkedomics and StarBase were used to investigate the clinical significance of miR-200c-3p, along with associated gene targets. PCa tissues and adjacent normal tissues were used for the detection of miR-200c-3p expression. A lentivirus overexpressing mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 35 publications
4
17
0
Order By: Relevance
“…Physiologically, ZEB2, a zinc finger homeodomain, functions as a molecular master switch during the EMT process that occurs in tumor aggression, including BC 27‐29 . Recently, ZEB2 has gained attention for its pro‐oncogenic functions: overexpression of ZEB2 contributes to the degree of malignancy, rapid cell proliferation, and poor patient survival in different tumors, and knockdown of ZEB2 expression inhibits cell proliferation, migration, and invasion 28,30,31 . Based on biomedical databases query and previous reports, 10,32 we confirmed that miR‐338‐3p could directly bind to ZEB2 3’UTR, as evidenced by dual‐luciferase reporter assay and Western blot assay.…”
Section: Discussionsupporting
confidence: 62%
“…Physiologically, ZEB2, a zinc finger homeodomain, functions as a molecular master switch during the EMT process that occurs in tumor aggression, including BC 27‐29 . Recently, ZEB2 has gained attention for its pro‐oncogenic functions: overexpression of ZEB2 contributes to the degree of malignancy, rapid cell proliferation, and poor patient survival in different tumors, and knockdown of ZEB2 expression inhibits cell proliferation, migration, and invasion 28,30,31 . Based on biomedical databases query and previous reports, 10,32 we confirmed that miR‐338‐3p could directly bind to ZEB2 3’UTR, as evidenced by dual‐luciferase reporter assay and Western blot assay.…”
Section: Discussionsupporting
confidence: 62%
“…Two online tools, including Target scan [34] and TACCO [35], were used to screen for candidate microRNAs probably targeting SFTPC mRNA to suppress its protein expression. StarBase was utilized to predict the association between miR-629-3p expression and SFTPC expression in LUAD [36].…”
Section: Bioinformatics Analysismentioning
confidence: 99%
“…hindered liver cancer malignant behavior via inactivation of WNT/β-catenin pathways (Zhang et al 2019c). Zhang and colleagues proved that the ZEB2/miR-200c loop participated in prostate carcinoma progression (Zhang et al 2019a). We found crosstalk between ZEB2 and canonical WNT/β-catenin pathways, which are frequently activated in GBM progression, providing attractive therapeutic targets against GBM.…”
Section: Discussionmentioning
confidence: 60%